YB-1 And CTCF Differentially Regulate The 5-HTT Polymorphic Intron 2 Enhancer Which Predisposes To A Variety Of Neurological Disorders. - Klenova, Elena; C. Scott,, Alison; Roberts, Julian; Shamsuddin, Shaharum; A. Lovejoy, Elizabeth; Bergmann, Stephan; J. Bubb, Vivien; Dieter Royer, Hans; P. Quinn, John (2004)

(untitled)
Mutation or inappropriate expression of the serotonin transporter (5-HTT) gene has been postulated as a possible predisposing factor in many CNS-related disorders, including numerous studies of affective disorders. The human gene encompasses 15 exons spanning -31 kb on chromosome 17qll (Lesch et aI., 1994).